Effect of Solvent Amount and Sugar on Chemical Traits of Instant (Curcuma xanthorrhiza Roxb.) - Azis, Nur Afni; Pujimulyani, Dwiyati; Setyowati, Astuti (Jurnal Biologi Tropis, 2025)
Temulawak, also known as Curcuma xanthorrhiza Roxb., is a long-used medicinal plant that is frequently utilized as an ingredient in traditional medicine. At harvest, the ginger rhizome has 80–90% water content. When ginger is harvested with a high water content, its quality declines and its selling price drops. The purpose of this study is to ascertain how variations in the concentrations of sugar and water affect the color and chemical characteristics of temulawak powder.  Water content, flavonoid and tannin levels, and antioxidant activity were all tested as part of the analysis. The data was statistically calculated using the Complete Randomized Block Design, and analysis of variance (ANOVA) was carried out at a 95% confidence level. whether the actual differences in each therapy were shown by the Duncan Multiple Range Test (DMRT). The findings demonstrated that the water content, flavonoid levels, tannin levels, and antioxidant activity are all significantly impacted by the amount of water and the addition of sugar. When 100 ml of water and 100 g of sugar are mixed together, the temulawak powder's water content is 3.01%, its flavonoid content is 1.73 mg GAE/g bk, its tannin content is 10.99 mg/100g, and its antioxidant activity is 83.30% RSA.